The Effect of Compositing Poultry manure with Zeolite on N, P, and K leaching in Greenhouse Agriculture: Column Study - يونس, سليمان; غياث علوش ,; ليلى حبيب, (Latakia University Journal -Biological Sciences Series, 2023)
A column study was conducted (25 cm Diameter) filled with Al-Hatra soil for a depth of 40 cm, in a greenhouse located in Tishreen University in 2022. Treatments were: poultry manure compost (OM), poultry manure composted with zeolite (OMZ), poultry manure compost and zeolite added after composted to the cultivation medium (OM + Z), In addition to the control treatment without adding compost (CONTROL). OM treatments received Poultry manure at a rate of 8%. All treatments received basic N, P, and K fertilization and columns were planted with tomato seedlings (Bastona Hybred), one plant per column and drip irrigated regularly weekly which contained additional 2 g soluble fertilizer every 15 days as according to stage of plant growth. Leachates were collected weekly and over 98 days, in which ammonium, Molybdate reactive P (MRP), potassium and the electrical conductivity (EC) were measured. Leaching of ammonium, phosphorus and potassium was higher in the presence of compost compared to the control treatment. Ammonium leaching start rapidly at start and then decline. The cumulative leaching of Ammonium from compost treatment was (OM) 472.5 mg NH4-N/plant/column, of which 88% leached within 28 days of the start of the experiment. Phosphorus leaching increased over time, and constitute after 98 days 22.8 and 37.7 mg/plant/column in the control and OM treatments, respectively, whereas, leaching of potassium remains constant over time. The addition of zeolite during composting (OMZ) or after composting (OM+Z) reduced ammonium leaching by 48% and 36% and potassium by 21% and 19%, respectively, compared with the OM treatment. Zeolite did not reduce phosphorus leached from columns. The cumulative quantities of leached NH4, MRP, and K correlated linearly with the amounts of leached water. Correlation coefficients were R2≥0.882 for phosphorus and R2≥0.986 for potassium in the OM treatments. As for NH4, the amount leached increased with increasing water leaching to 5.74 liter, in which carried 88% of the total quantity of leached NH4